Total quality management and halal certification of food product in Malaysia / Rizuwan Abu Karim … [et al.] - Abu Karim, Rizuwan; Mahmud, Nurazree; Abu Hasan, Helmy Fadlisham; Sa‘ari, Juan Rizal (2017)
This paper principally discusses on conceptualization of model related to Total Quality Management (TQM) and halal certification of food product in Malaysia. Six critical success factors of TQM has been discussed in relations to halal certification of food product. Based on previous studies, it is proved that TQM practices influence the successfulness of halal certification of food products. Hypothesis pertaining the two variables of this study has been proposed in effort to describe the idea of TQM and halal certification of food products. Future research is suggested in order to obtain empirically evidence in establishing the real impact of TQM practices either soft or hard factors will more influence successful of halal certification of food products.